University social responsibility, management and educational policies: A critical discourse analysis - Cabanzo Carreño, Carlos Jairo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The university is the object of permanent scrutiny and analysis, both for its historical importance, its academic heritage and its discursive production. Thus, the concept of university social responsibility (RSU), of business origin, generates a framework for university orientation and organization. The objective of this article is to reveal the discourses from which the concept of USR permeates the management and university educational policies in Colombia. Through the critical discursive analysis (CDA) carried out, it is found that USR affects higher education institutions (HEIs), at the levels of government, social projection, ethical training - citizenship and social management of knowledge, among others.